Filter medias from recycled concrete, properties investigated for sorption processes - Žurauskienė, Ramunė; Valentukevičienė, Marina; Boussouga, Youssef-Amine (International Conference “Environmental Engineering”, 2017)
Every year construction demolition waste amount increases. 75 percent of this waste consists of concrete, masonry products and tile products. Concrete and reinforced concrete waste can be recycled and reused for new concrete product pro duction, road installation, as well as formed water treatment. Crushed concrete particles are characterized by large surface area and many voids. These particle characteristics depend on used crushing-granulating method. Particles obtained by the milling method have larger number of voids, higher water absorbance and higher number of open pores. Crushed concrete particles, of which high amounts are formed in building or waste recycling sites, can be used as filler for water treatment filters.